Pengembangan Modul Elektronik Menggunakan Website Heyzine Flipbooks pada Pembelajaran Sejarah Kelas X - Ricu Sidiq; Fatma Nur Azhari; Sandi Tamara Peranginangin; Wulan Dari Br Nababan; Kasih Candra (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to: (1) produce an electronic module for the History subject of class X, (2) determine the level of eligibility of the electronic module for the History subject of class X, and (3) determine the effectiveness of using the electronic module product in improving learning outcomes in the History subject of class X. This development research refers to the steps developed by Sugiyono, namely Borg and Gall. The development procedure includes: 1) potential and problems, 2) data collection, 3) product design, 4) design validation, 5) design revision, 6) initial trial, 7) product revision, 8) usage trial, and 9) product revision. The subjects of the field trial were 35 students of class X E-6 of SMA Negeri 10 Medan. Data collection used assessment sheets, response questionnaires, and learning outcome tests. The results of the study showed that the electronic history module was declared feasible to be used as teaching material in schools with an average score of material experts of 94% and an average score of media experts of 99%, an average score of small group trials of 84.5%, and participant responses as large-scale users of 87.5% so that the feasibility of the developed electronic history module falls into the category of "very good". The effectiveness of the electronic history module was analyzed based on the results of the pre-test and post-test, it was found that the post-test score was higher than the pre-test. The percentage of N-Gain obtained was 0.8% with the category of "very effective". Through the results of the feasibility and effectiveness assessment, it was obtained that the electronic history module product for class X of SMA Negeri 10 Medan was very feasible and very effective to be used in the history learning process.